Isolation of Bacteria from Raw Milk Collected at Milk Super Markets in Tripoli City - Salah Altwanesy,; Abdulfatha Abokridighah, (AlQalam Journal of Medical and Applied Sciences, 2024)
Globally, billions of people consume milk and dairy products every day. Milk samples were collected at 15 milk collection centers (milk super market). According to stratified random sampling design. Samples were analyzed for Total Plate Count (TPC). The prevalence of selected pathogens such as Listeria monocytogenes, E. coli and Salmonella was determined. The mean counts per ml for TPC, psychrotrophs and thermophiles were 12×106, 7.5×103 and 9.1×103, respectively. A TPC less than 106 cfu ml−1 was used as a basic standard by MCC in the Price Incentive Programme. From the 150 milk samples tested, approximately 90% were contaminated by coliform bacteria and 65% were E. coli positive, with mean counts ranged from 103 to 104 cfu ml−1. S. aureus was isolated from more than 60% of the samples and the mean count per ml was 12×103. Meanwhile, E. coli was also detected in20 (33.5%) samples. However, Salmonella was only detected in 1.4% of the samples, with the Central region having the highest frequency of isolation. Thirteen Salmonella serotypes were identified, including S. muenchen, S. anatum and S. agona. A total of 47 strains of Listeria were isolated from 4.4% Listeria-positive samples including L. monocytogenes (1.9%), L. innocua (2.1%) and L. welshimeri (0.6%). The presence of pathogenic bacteria such as E. coli, Salmonella and Listeria spp. in raw milk is of public health concern since drinking raw milk is still considered good for health in rural population. على مستوى العالم، يستهلك مليارات الأشخاص الحليب ومنتجات الألبان كل يوم. تم جمع عينات الحليب من 15 مركزًا لجمع الحليب (سوبر ماركت الحليب). وفقًا لتصميم أخذ العينات العشوائية الطبقية. تم تحليل العينات لمعرفة إجمالي عدد الأطباق (TPC). تم تحديد انتشار مسببات الأمراض المختارة مثل Listeria monocytogenes و E. coli و Salmonella. كان متوسط الأعداد لكل مل لـ TPC والبكتيريا المحبة للحرارة والبكتيريا المحبة للحرارة 12 × 106 و 7.5 × 103 و 9.1 × 103 على التوالي. تم استخدام TPC أقل من 106 cfu ml-1 كمعيار أساسي من قبل MCC في برنامج الحوافز السعرية. من بين 150 عينة حليب تم اختبارها، كان ما يقرب من 90٪ ملوثًا بالبكتيريا القولونية و 65٪ كانت إيجابية لـ E. coli، مع متوسط الأعداد يتراوح من 103 إلى 104 cfu ml-1. تم عزل S. aureus من أكثر من 60٪ من العينات وكان متوسط العدد لكل مل 12 × 103. وفي الوقت نفسه، تم الكشف عن الإشريكية القولونية أيضًا في 20 عينة (33.5%). ومع ذلك، تم الكشف عن السالمونيلا في 1.4% فقط من العينات، حيث كانت المنطقة الوسطى هي الأعلى تواترًا للعزل. تم تحديد ثلاثة عشر نوعًا مصلًا من السالمونيلا، بما في ذلك S. muenchen وS. anatum وS. agona. تم عزل ما مجموعه 47 سلالة من الليستيريا من 4.4% من العينات الإيجابية للليستيريا بما في ذلك L. monocytogenes (1.9%) وL. innocua (2.1%) وL. welshimeri (0.6%). إن وجود البكتيريا المسببة للأمراض مثل الإشريكية القولونية والسالمونيلا والليستيريا في الحليب الخام يشكل مصدر قلق للصحة العامة حيث لا يزال شرب الحليب الخام يعتبر جيدًا للصحة في المناطق الريفية